2012
DOI: 10.4103/0253-7613.91876
|View full text |Cite
|
Sign up to set email alerts
|

Role of acamprosate in sensorineural tinnitus

Abstract: Acamprosate with dual mechanism of action as glutamate antagonist and GABA agonist can be a potential target to decrease the severity of sensorineural tinnitus.Objective:(1)To study the effectiveness of acamprosate in providing subjective relief and objective improvement in patients having tinnitus of sensorineural origin. (2) To evaluate the adverse events related to the use of acamprosate and also determine the change in quality of life (QOL) parameters.Materials and Methods:The study was randomized double-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 14 publications
1
32
0
1
Order By: Relevance
“…36 Whereas the review identified 6 studies that favored treatment over control for tinnitusspecific QOL outcomes [169][170][171][172][173][174] and 5 studies that favored treatment over control for subjective tinnitus loudness outcomes, 169,[173][174][175][176] selection and other bias, small sample sizes, and imprecise effect estimates led to an assessment of low or insufficient strength of evidence for these outcomes.…”
Section: Supporting Textmentioning
confidence: 99%
“…36 Whereas the review identified 6 studies that favored treatment over control for tinnitusspecific QOL outcomes [169][170][171][172][173][174] and 5 studies that favored treatment over control for subjective tinnitus loudness outcomes, 169,[173][174][175][176] selection and other bias, small sample sizes, and imprecise effect estimates led to an assessment of low or insufficient strength of evidence for these outcomes.…”
Section: Supporting Textmentioning
confidence: 99%
“…Acamprosate was shown to quieten tinnitus in two well-designed studies (Azevedo and Figueiredo, 2005;Sharma et al, 2012) but was said not to be effective in a third as yet unpublished study (Martin, 2011). One of the studies found that at 90 days the tinnitus was not heard in more than 10% of subjects (Sharma et al, 2012).…”
Section: Treatment Of Tinnitusmentioning
confidence: 99%
“…In an RCT (n=40), participants with tinnitus received acamprosate or placebo for 45 days, followed by a washout period of 1 week 23. Acamprosate reduced the tinnitus score in more participants than placebo (any reduction [i.e.…”
Section: Drug Treatmentmentioning
confidence: 99%
“…benzodiazepines) as GABA is thought to be inhibitory in the auditory pathway 1,23. A systematic review found one high-quality RCT comparing alprazolam with chlorphenamine, which reported no significant difference in the THI (d=0.07 [not significant]) 7…”
Section: Drug Treatmentmentioning
confidence: 99%